PWE-015 Clinical efficacy and safety of anti-TNF therapy in inflammatory bowel disease in the elderly. (8th June 2018) - Digby-Bell, Jonathan; Ibraheim, Hajir; Badrulhisham, Fakhirah; Powell, Nick
Abstract : Introduction: Many patients, especially the elderly, are excluded from clinical drug trials and little real-life data exists on the safety and efficacy of anti-TNF in this comorbid and difficult to treat group. We wanted to compare the clinical efficacy and safety of anti-TNF therapy in patients over 60 years in a tertiary IBD centre in London. Methods: We interrogated our IBD biologics database from January 2009 to November 2015 and performed retrospective data analysis until end of follow up in April 2017. Data was collected on demographics, biochemistry and clinical scores. For every '≥60' patient identified we randomly selected two '<60' comparators. Primary endpoints: week 14 and week 54 steroid free clinical remission (Harvey Bradshaw Index<5 or Simple Colitis Activity index <3). Secondary endpoint: proportion of patients remaining on anti-TNF at the end of follow up Results: 29 patients (23 Crohn's, 4 ulcerative colitis, 1 IBD unclassified) started anti-TNF aged '≥60' and 58 randomly chosen <60 years were selected for analysis. Conclusions: Only a small number of '≥60' patients started anti-TNF (29 out of greater than 650). This may reflect our local population, less severe disease or that clinicians favour non anti-TNF therapies in this older group. Overall there was similar clinical efficacy at weeks 14 and 54 of anti-TNF therapy between the 'young' and 'old' groups. There was a statistically significantly higher discontinuation rate after 1 year of therapy in the older group (p=0.043). There were more adverse events in the older group (7/29), including 3 new cancer diagnoses, compared with the younger group (4/58). 4 patients had detectable anti-drug antibodies in the older group despite 2 of them having therapeutic thiopurine suggesting that the elderly may have more immunogenicity than the young. Further studies with more patients across multiple sites are required to clarify safety and efficacy of anti-TNF therapy in the elderly.